KNOWLEDGE AND PRACTICES OF INFANT AND TODDLERS WEANING AMONG MOTHERS ATTENDING PEDIATRICS DEPARTMENT OF A TERTIARY CARE HOSPITAL - Dr Misbah Ullah Khan; Dr Tanzeela; Dr Noor Ul Haram Khattak; Dr Sadiq Akbar; Dr Ruba Gul; Dr Zia Muhammad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Weaning is a critical stage in an infant’s development that involves introducing complementary foods alongside continued breastfeeding. Improper weaning practices can lead to malnutrition, infections, and growth issues in children.Objective: To assess the knowledge and practices regarding weaning among mothers attending the Pediatrics Department of a tertiary care hospital in Pakistan.Materials and Method: A descriptive cross-sectional study was conducted at Khyber Teaching Hospital, Peshawar, from January 2024 to June 2024. A total of 200 mothers of infants aged 6–24 months were selected using convenience sampling. Data were collected using a structured questionnaire and analyzed using SPSS version 25.Results: While 68% of mothers knew the recommended age for weaning, 40% did not follow WHO guidelines. Only 60% introduced appropriate foods, and maternal education significantly influenced feeding practices.Conclusion: There is a gap between maternal knowledge and practice regarding weaning. Educational interventions are needed to promote proper weaning practices.